Institutional adaptation to climate variability in South Africa: a study of Buffalo City Metropolitan Municipality in Eastern Cape. - Gadu, Siyaxola Ernest (My University, 2019)
South Africa is a country that is vulnerable to the changing climate and must adapt adequately to this phenomenon. Existing institutional and policy framework is the foundation in place to allow the government to adapt to climate change, however, the results are not yet satisfactory, especially to point whereby the expectations of the all stakeholders are met. Although climate change adaptation policies, plans and strategies are in place, the extent to which climate change is integrated within development plans and strategies at local government level is limited. The research findings indicate that consideration of climate change adaptation, with specific focus on agriculture and water resources, within development plans of Buffalo City Metropolitan Municipality (BCMM) is limited due to several reasons such as: the structure of institutional and policy framework of South Africa, institutional fragmentation, lack of capacity, poor prioritisation and uncertainty of climate change. Community-based adaptation (CBA) is one of the dominating adaption techniques in developing countries. The success of this climate change adaptation method is limited to areas with certain characteristics, and it cannot be used in regions with different features. This study sheds light on reasons that limit the reach of CBA when compared to institutional adaptation when it comes to tackling the scourge of climate change.
Dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, October 2019